2015
DOI: 10.1016/j.drugalcdep.2015.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Independent effects of HIV infection and cocaine dependence on neurocognitive impairment in a community sample living in the southern United States

Abstract: Background Prior studies have established that methamphetamine and HIV can have additive deleterious effects on neurocognitive functioning, but there has been relatively little research on other stimulants like cocaine. This study investigated the effects of cocaine and HIV on neurocognitive impairment in a large, well-characterized sample. Methods The sample included 193 adults across four groups: HIV-positive cocaine users (n=48), HIV-negative cocaine users (n=53), HIV-positive non-drug users (n=60), and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 66 publications
1
28
0
2
Order By: Relevance
“…By contrast, we found no evidence of selective visual memory impairment among HIV+ cocaine-dependent men, consistent with previous reports of varying neurocognitive effects of cocaine use among primarily male HIV+ participant samples (Durvasula et al, 2000; Meade, Conn, Skalski, & Safren, 2011; but cf. Meade, Towe, Skalski, & Robertson, 2015). More basic and clinical studies are needed to characterize the increased risk of neurocognitive impairment among HIV+ cocaine-dependent women in more detail and to address the question of whether this vulnerability is HIV-specific; we note that regardless of HIV serostatus, women are more vulnerable to stimulant addiction than men: The addiction literature indicates that women escalate their use of stimulants more rapidly, and relapse more readily, than men (Becker & Hu, 2008; Greenfield, Back, Lawson, & Brady, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, we found no evidence of selective visual memory impairment among HIV+ cocaine-dependent men, consistent with previous reports of varying neurocognitive effects of cocaine use among primarily male HIV+ participant samples (Durvasula et al, 2000; Meade, Conn, Skalski, & Safren, 2011; but cf. Meade, Towe, Skalski, & Robertson, 2015). More basic and clinical studies are needed to characterize the increased risk of neurocognitive impairment among HIV+ cocaine-dependent women in more detail and to address the question of whether this vulnerability is HIV-specific; we note that regardless of HIV serostatus, women are more vulnerable to stimulant addiction than men: The addiction literature indicates that women escalate their use of stimulants more rapidly, and relapse more readily, than men (Becker & Hu, 2008; Greenfield, Back, Lawson, & Brady, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that in some human immunodeficiency virus-1 (HIV) infected individuals, the development of HIV associated neurocognitive disorders (HAND) is accelerated and/or its severity increased with substance abuse, in the absence or presence of prescribed combination antiretroviral therapy (cART) (Rippeth et al, 2004; Hauser et al, 2007; Buch et al, 2012; Meyer et al, 2013; Weber et al, 2013; Meade et al, 2015). The mechanisms by which substance abuse contributes to HIV neuropathogenesis are not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Substance abuse is also associated with poor adherence to prescribed cART (Arnsten et al, 2002; Hinkin et al, 2007) and with increased HIV neuropathogenesis (Rippeth et al, 2004; Hauser et al, 2007; Buch et al, 2012; Meyer et al, 2013; Weber et al, 2013; Meade et al, 2015). Drugs of abuse, including cocaine and methamphetamine, increase extracellular concentrations of dopamine in the CNS (Volkow et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis concluded that cocaine users perform worse than controls on a range of neuropsychological tests (Spronk et al , 2013). Moreover, prior studies have demonstrated that chronic cocaine use is associated with greater neurocognitive impairment in HIV-infected persons (Meade et al , 2011; Meade et al , 2015; Nath et al , 2001). DTI studies provide preliminary evidence that chronic cocaine use is associated with reduced FA, particularly in the corpus callosum and frontal and parietal lobes, but cocaine does not appear to affect MD (Kelly et al , 2011; Lane et al , 2010; Lim et al , 2002; Lim et al , 2008; Ma et al , 2009; Ma et al , 2015; Moeller et al , 2005; Moeller et al , 2007; Romero et al , 2010).…”
Section: Introductionmentioning
confidence: 99%